Analisis Teknik Dasar Pukulan Backhand Pada Permainan Bulu Tangkis Pb Buana Sakti Kota Lubuklinggau - Pujangga Pujangga; Leo Charli; Hengky Remora (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe the Basic Techniques of Backhand Overhead Badminton in PB Buana Sakti Watervang, Lubuklinggau City. This research is a type of qualitative descriptive research. The subject of this research is the badminton coach and student of PB Buana Sakti Watervang Lubuklinggau City. Data collection techniques were carried out by interview, observation, and documentation. Data were analyzed using components recommended by Yuliawan and Tony Grice. Data collection was carried out during the day after collecting all the data directly analyzed. The results showed that the value of the movement on the basic technique in short serve badminton in PB. Buana Sakti said that of the 13 participants who took the observation, interview and documentation test, they were coaches and students, that the basic technique of hitting Backhand Overhead PB. Buana Sakti Watervang, when viewed from the aspect of observation based on the ability of the participants, that the basic technique of hitting Backhand Overhead PB. Buana Sakti watervang has good results. Keywords: Basic Techniques, Badminton and Backhand Overhead.